Influence of polycarboxylate superplasticizer, citric acid and their combination on the hydration and workability of calcium sulfoaluminate cement. (September 2021) - Belhadi, Rachid; Govin, Alexandre; Grosseau, Philippe
Abstract: PCEs are well known to improve the initial fluidity of CSA. However, their dispersion efficiency drops quickly over time. This issue can be solved by incorporating retarders. In this context, this paper deals with the influence of citric acid, used as a retarder, PCE and their combination on the hydration and workability of CSA. Isothermal calorimetry, XRD and TG analysis were used to describe the hydration process, while workability was characterized with the mini-cone test. Adsorption behavior was investigated using total organic carbon analyzer coupled with ion chromatography. Results show that the introduction of citric acid retained the dispersion efficiency of PCE over time. However, the initial dispersion efficiency of PCE was decreased by citric acid as the latter tend to adsorb first on the surface of cement grains, inhibiting the adsorption of PCE. A dispersion model was proposed to describe the acting mechanism of these admixtures on CSA. Highlights: The dispersion efficiency of polycarboxylate superplasticizers drops quickly over time. Citric acid maintains the dispersion efficiency of PCE over time. Competitive adsorption between citric acid and PCE occurs. The combination of citric acid with PCE decreases the initial dispersion efficiency of PCE.